TINGKAT SPESIALISASI INDUSTRI AUDITOR SEBAGAI PEMODERASI PENGARUH UKURAN PERUSAHAAN PADA AUDIT DELAY - Senjaya, Karina; Suprasto H., Bambang (E-Jurnal Akuntansi, 2016)
This study aimed to examine the effect of firm size to audit delay with auditor industry specialization level as moderating variables. This research was conducted in mining companies listed on the Stock Exchange in 2010-2014. The total sample is 13 companies. The sampling method used is nonprobability sampling with purposive sampling technique. The analysis technique used is moderated regression analysis (MRA). This study shows that the size of the company negatively affect audit delay and auditor industry specialization level capable to reinforced negative relationship between those variables. Companies with larger size generally faced with greater external pressure to deliver their financial statements so the audit delay tends to be shorter. While the industry specialization give auditors more knowledge about client’s company, so that despite the large size of the client company, with the knowledge that better in finding mistake from financial statements, then audit delay will be shorter.
Keywords: audit delay, company size, auditor industry specialization levels